Socio-economic, biological, psychological and behavioural factors associated with health-related quality of life among adolescents in Kuala Lumpur - V. Sanker, Kaartina (2015)
Poor health-related quality of life (HRQoL) is no longer associated with only overweight and obesity as evidence shows that there are other factors contributing towards HRQoL. Thus, the aim of this study is to determine the association between socio-economic, biological, psychological, behavioural factors and HRQoL among adolescents in Kuala Lumpur, Malaysia. A cross-sectional multistage study was carried out in five selected schools in the Federal Territory of Kuala Lumpur. A total of 501 Malaysian students (male: 42.0%; female: 58.0%) aged between 13-17 years participated in this study. Majority of the respondents were Malays (49.0%), 39.0% were Chinese, 9.0% were Indians and 3.0% were of other ethnic groups. Respondents were required to complete a Two-day Dietary Recall, Two-day Physical Activity Recall, Pubertal Development Scale, Multi-dimensional Body Image Scale, Depression, Anxiety and Stress Scale, Rosenberg Self-esteem Questionnaire, Nutrition Knowledge Questionnaire, Eating Behavior Questionnaire, Three Factor Eating Questionnaire and PedsQL TM 4.0 Generic Core Scale. The mean score for total HRQoL was 74.1 ± 16.3. As for the HRQoL dimension, the highest score was obtained in the social function (80.4 ± 19.7), followed by physical function (78.2 ± 18.5) school function (71.0 ± 19.4) and emotional function (67.0 ± 21.9). Parental monthly income (r= 0.109, p<0.05), father (r= 0.105, p<0.05) and mother total years of schooling (r= 0.132, p<0.05) had significant associations with total HRQoL score. There was a weak relationship between age and total HRQoL score (r=0.126, p<0.01). There was a significant difference in the total HRQoL score between the ethnic groups whereby Indian respondents obtained the highest score whereas Malay respondents demonstrated lowest score (F=5.205, p<0.05). Further, all psychological factors (depression, anxiety, stress, body image, self-esteem, nutrition knowledge) were associated with total HRQoL score (r=-0.545, p<0.01; r=-0.542, p<0.01; r=-0.528, p<0.01; r=-0.200, p<0.01; r=0.302, p<0.01; r=0.178, p<0.01) respectively. Total energy intake/body weight and carbohydrate intake were negatively significantly correlated with total HRQoL score (r= -0.145, p<0.05; r= -0.113, p<0.01). Respondents who had regular main meals reported better overall HRQoL (r=0.181, p<0.01) while respondents who snacked between main meals demonstrated poor HRQoL (t=2.496, p<0.05). Next, respondents who demonstrated higher scores in the cognitive restraint, emotional eating and uncontrolled eating subscale reported lower total HRQoL score (r=-0.135, p<0.01; r= -0.238, p<0.01; r= -0.150, p<0.01) respectively. Respondents with higher energy expenditure/body weight were reported to have better HRQoL when compared to their counterpart (r=0.166, p<0.01), whereas respondents who spent more time on screen based media (SBM) showed poor HRQoL (r= -0.444, p<0.01). However, there was no significant association between sex (t=0.858, p=0.391), BMI-for-age (r=0.120, p=0.938), body weight status (F=0.178, p=0.837), pubertal stage (F=2.157, p=0.073), perceived pubertal timing (F=1.29, p=0.855), fat (r=-0.021, p=0.144) and protein intake (r=-0.066, p=0.644), family meal frequency (F=2.062, p=0.069) and physical activity level (F=1.96, p=0.838) with total HRQoL score. A six factor-model which comprises depression, anxiety, SBM, ethnicity (Indian), carbohydrate intake, and meal frequency explain 45.4% of the variances in HRQoL among adolescents (R2=0.454) was derived using the Multiple Linear Regression. This study suggests that low risk of depression and anxiety, decreased SBM usage, being an Indian, decreased carbohydrate intake and increased main meal frequency would result in good HRQoL among respondents in Kuala Lumpur Malaysia.Thus, program planner should consider psychological factors, ethnicity difference and healthy eating behaviour in implementing intervention to improve HRQoL among adolescents.